The Dreyfus Affair and its Reflection in Ladino Literature - Dori, Nitsa (International Journal of Emerging Trends in Social Sciences, 2018)
The Dreyfus Affair took place in the fall of 1894, when secret documents sent by a French officer to the attaché of the German embassy in Paris fell into the hands of the French intelligence services. Based on some similarity in the handwriting, and apparently also because of anti-Jewish prejudice, the intelligence service heads suspected Alfred Dreyfus, a Jewish officer in the French army. The court unanimously found Dreyfus guilty of treason, and he was sentenced to be stripped of his rank and to life imprisonment. The purpose of this article is to reflect the literary expression of the Dreyfus Affair in Ladino literature. The article will discuss several genres of literature in Ladino about the Dreyfus Affair during different periods: two historical novels, two plays, and a newspaper article, while examining the correspondence between the different compositions.